2022
DOI: 10.3390/vetsci9040186
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of the Global Distribution of Causes and Syndromes Associated with Mid- to Late-Term Pregnancy Loss in Horses between 1960 and 2020

Abstract: Equine pregnancy loss is frustrating and costly for horse breeders. The reproductive efficiency of mares has significant implications for a breeding operation’s economic success, and widespread losses can have a trickle-down effect on those communities that rely on equine breeding operations. Understanding the causes and risks of equine pregnancy loss is essential for developing prevention and management strategies to reduce the occurrence and impact on the horse breeding industry. This PRISMA-guided scoping r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 52 publications
(61 reference statements)
1
21
0
Order By: Relevance
“…were the most prevalent, which agrees with previous reports. 14,15,17,19,24 Streptococcus spp. are part of the normal microbiota of the genital canal, but they can invade the uterus and cause endometritis, ascending placentitis, and fetal death opportunistically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were the most prevalent, which agrees with previous reports. 14,15,17,19,24 Streptococcus spp. are part of the normal microbiota of the genital canal, but they can invade the uterus and cause endometritis, ascending placentitis, and fetal death opportunistically.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several infectious agents known to cause reproductive losses in horses are zoonotic and/or have a major impact on international trade. 15…”
mentioning
confidence: 99%
“…Induction of ovulation has been found to reduce the risk of EPL (de Mestre et al 2019), possibly acting via the quality of the ovulated oocyte or early luteal function (Köhne et al 2014). Whilst not epidemiological studies are lacking, it is still clear that the presence or absence of pathogens is key to pregnancy loss (Macleay et al 2022) as demonstrated by the marked geographic variation in reporting of certain pathogens.…”
Section: External/environmental Level Risk Factorsmentioning
confidence: 99%
“…Broadly, losses fall into two categories, infectious and noninfectious. A recent scoping review of mid and late gestational losses indicates the intensive interest of the research community in infectious causes of pregnancy loss with studies of placentitis, EHV-1, Chlamydia, Leptospirosis and Nocardioform placentitis dominating the literature of the last three decades (Macleay et al 2022). Equally, once we drill down to individual populations, the picture can look quite different.…”
Section: Causes Of Pregnancy Lossmentioning
confidence: 99%
See 1 more Smart Citation